问题 解答题
已知首项为1的数列{an}满足:对任意正整数n,都有:a12
a1
-1
+a22
a2
-1
+a32
a3
-1
+…+an2
an
-1
=(n2-2n+3)•2n+c
,其中c是常数.
(Ⅰ)求实数c的值;
(Ⅱ)求数列{an}的通项公式;
(Ⅲ)设数列{
an
(-
1
2
)
an
-1
}
的前n项和为Sn,求证:S2n-1>S2m,其中m,n∈N*
答案

(Ⅰ)当a=1时,1×20=2×2+c,

解得c=-3.

(Ⅱ)∵a12

a1
-1+a22
a2
-1
+a32
a3
-1
+…+an2
an
-1
=(n2-2n+3)•2n+c,①

a12

a1
-1+a22
a2
-1
+a32
a3
-1
+…+an-12
an-1
-1
=[(n-1)2-2(n-1)+3]•2n-1+c,②

①-②,并整理,得an2

a n
-1=n22n-1

∴an=n2

(Ⅲ)∵an=n2

∴数列{

an
(-
1
2
)
an
-1
}={n•(-
1
2
)
n-1
}.

∴S2n-1=1+2(-

1
2
) +3(-
1
2
)
2
+…+(2n-1)•(-
1
2
)
2n-2

-

1
2
S2n-1=1(-
1
2
)
 
+2(-
1
2
)
2
+…+(2n-2)•(-
1
2
)
2n-2
+(2n-1)•(-
1
2
)
2n-1

3
2
S2n-1=1+(-
1
2
)
 
+(-
1
2
)
2
+…+(-
1
2
)
2n-2
-(2n-1)•(-
1
2
)
2n-1

=

1×[1-(-
1
2
)
2n-1
]
1-(-
1
2
)
=
2
3
[1-(-
1
2
)
2n-1
]

S2n-1=

4
9
[1-(-
1
2
)
2n-1
]
4
9

同理,S2m=

4
9
[1-(-
1
2
)
2m
]
4
9

∴S2n-1>S2m,其中m,n∈N*

填空题
单项选择题